Diplomazia e scienza: la politica antartica del Regno Unito nell’Anno geofisico internazionale, 1955-1959 - ELLI M (2008)
The essay deals with the International Geophysical Year, namely an interesting example of XIX-style scientific internationalism at the time of the Cold War. It focuses on the awkward position of the United Kingdom in Antarctica and more generally in Polar research in a period of increasing financial constraints. Confronted with overlapping territorial claims and of a Soviet encroachment in Antarctica even after the expire of the International Geophysical Year, British diplomats and scientists sought to thrive on the spirit of the IGY to press on a kind of 'condominium' that eventually turned in an actual internationalisation of Anctarctica for research purposes, which still holds nowadays. British thinking anticipated U.S. actions and was particularly useful in pressing in the urgency of a solution to Commonwealth countries involved (especially Australia).